2022
DOI: 10.1155/2022/5792312
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Mental Health Status and Quality of Life and Correlation among Patients with Permanent Stoma of Colorectal Tumor

Abstract: Background. Colorectal cancer is one of the malignant tumors of the digestive system relatively hidden onset with unobvious early clinical symptoms. Most patients have developed into middle and late stages when they were diagnosed, missing the best period of operation. Advanced colorectal cancer has strong diffusion and metastasis with short survival time, which seriously threatens the life safety of patients. Objective. To investigate the mental health status and quality of life and the relationship between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…To our knowledge, this is the rst study to identify the resilience subgroup of colorectal cancer patients with enterostomy using latent pro le analysis. In previous studies of resilience in colorectal cancer enterostomy patients, the researchers used only sample means and standard deviations to describe the overall level of resilience, and the results showed that the patients' resilience was moderate and above [8,31]. Therefore, it was di cult for the researcher to identify patients with low resilience, which in turn prevented the development of an intervention programme based on the characteristics of high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the rst study to identify the resilience subgroup of colorectal cancer patients with enterostomy using latent pro le analysis. In previous studies of resilience in colorectal cancer enterostomy patients, the researchers used only sample means and standard deviations to describe the overall level of resilience, and the results showed that the patients' resilience was moderate and above [8,31]. Therefore, it was di cult for the researcher to identify patients with low resilience, which in turn prevented the development of an intervention programme based on the characteristics of high-risk patients.…”
Section: Discussionmentioning
confidence: 99%